Pioglitazone Is a Mild Carrier-Dependent Uncoupler of Oxidative Phosphorylation and a Modulator of Mitochondrial Permeability Transition - Ekaterina S. Kharechkina; Anna B. Nikiforova; Konstantin N. Belosludtsev; Tatyana I. Rokitskaya; Yuri N. Antonenko; Alexey G. Kruglov (MDPI AG, 2021)
Pioglitazone (PIO) is an insulin-sensitizing antidiabetic drug, which normalizes glucose and lipid metabolism but may provoke heart and liver failure and chronic kidney diseases. Both therapeutic and adverse effects of PIO can be accomplished through mitochondrial targets. Here, we explored the capability of PIO to modulate the mitochondrial membrane potential (ΔΨm) and the permeability transition pore (mPTP) opening in different models in vitro. ΔΨm was measured using tetraphenylphosphonium and the fluorescent dye rhodamine 123. The coupling of oxidative phosphorylation was estimated polarographically. The transport of ions and solutes across membranes was registered by potentiometric and spectral techniques. We found that PIO decreased ΔΨm in isolated mitochondria and intact thymocytes and the efficiency of ADP phosphorylation, particularly after the addition of Ca2+. The presence of the cytosolic fraction mitigated mitochondrial depolarization but made it sustained. Carboxyatractyloside diminished the PIO-dependent depolarization. PIO activated proton transport in deenergized mitochondria but not in artificial phospholipid vesicles. PIO had no effect on K+ and Ca2+ inward transport but drastically decreased the mitochondrial Ca2+-retention capacity and protective effects of adenine nucleotides against mPTP opening. Thus, PIO is a mild, partly ATP/ADP-translocase-dependent, uncoupler and a modulator of ATP production and mPTP sensitivity to Ca2+ and adenine nucleotides. These properties contribute to both therapeutic and adverse effects of PIO.